Extreme ultraviolet and soft x-ray spectral lines in Rb XXIX. (25th January 2016) - Khatri, Indu; Goyal, Arun; Aggarwal, Sunny; Singh, A K; Mohan, Man
Abstract: An extensive theoretical set of atomic data for Rb XXIX in a wide range with L -shell electron excitations to the M -shell has been reported. We have computed energy levels for the lowest 113 fine structure levels of Rb XXIX. The fully relativistic multiconfigurational Dirac–Fock method (MCDF) within the framework of Dirac–Coulomb Hamiltonian taking quantum electrodynamics (QED) and Breit corrections into account has been adopted for calculations. Radiative data are reported for electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2), and magnetic quadrupole (M2) transitions from the ground level, although calculations have been performed for a much larger number of levels. To assess the accuracy of results, we performed analogous calculations using flexible atomic code (FAC). Comparisons are made with existing available results and a good agreement has been achieved. Most of the wavelengths calculated lie in the soft x-ray (SXR) region. Lifetimes for all 113 levels have also been provided for the first time. Additionally, we have provided the spectra for allowed transitions from n = 2 to n = 3 within the x-ray region and also compared our SXR photon wavelengths with experimentally recognized wavelengths. We hope that our results will be beneficial in fusion plasma research and astrophysical applications.